Physical and physiological characteristics of male handball players: influence of playing position and competitive level - Haugen, T. A.; Tonnessen, E.; Seiler. S. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to quantify differences in anthropometrical and physical characteristics according to playing position and competitive level in male elite handball. METHODS: One hundred and seventy-six national team and 1st division players (age 23±4 years, body mass 89±11 kg, body height 188±5 cm) participated in the study. All participants were tested on throwing velocity, 20-meter sprint, countermovement jump, 3000-meter run, 1RM squat and bench press. RESULTS: Back players achieved higher throwing velocities compared to other positions. National team back players achieved higher velocities in set shots (9.4%, PCONCLUSIONS: Varying on-court demands in handball are reflected by different physical and physiological characteristics across playing standard and positions. Physical conditioning of players should therefore be individualized and targeted to solve the position-dependent tasks during play.